(3GQJjGM GdNGWQ aj eYQaI GdChGNQs - (3eMeO Hf Ydj Hf CMeO Hf Ydj Hf NeGQhjg Hf Whdhf GdOeTbqj GdUGdMj GdMfaj, TeS GdOjf , J (B953 (3g` s
(3ChdgG (B:s
(3hHYO aEf GdYdeGA QVi Gddg Yfge bd Gf JQchG efgLkG eG Sdchg Gh HGHkG eG ONdhg GhafkG dWjakG eG GHJcQhg s
(3BNQgG (B:s
(3BNQ ef Qhi Yf CHj GdaJM eMeO Hf eMeO Hf GHQGgje GHf ehSi s
(3PcQ ajg GdChGNQ ef Gdedhc hGdCYdGe hGdCTjGAs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B291s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B367 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe LRA (B2/ 1 - (3U (B9 s
Keywords: (3GdJGQjNs